An Analysis of figurative language in the poem The Phoenix and the Turtle by William Shakespeare - Said, Ratna (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to figure out figurative language that used in the phoenix and the turtle works of Shakespeare . This study used library research, which focus on literal and non-literal meaning of figurative languages to make it easier to classifying data. The technique of analysis of the data is by reading, identifying, understanding, finding, and making conclusion every poems.The results of the study shows that the most dominant figurative language in the selected poems are seven Metaphor/alegory, eleven personification, theree simile and two symbol.